Assessment of Staff Exposure to Radon in Radiotherapy Centers in Tehran, 2015 - Arezoo Imani; Fereidoun Mianji; Vahid Changizi; Seyyed Hossein Mousavie Anijdan; Reza Paydar (Tehran University of Medical Sciences, 2017)
Background and Aim: Estimation of radon density  in underground centers is very important. Considering the use of high-energy medical accelerators, radiotherapy departments are usually located in underground floors. The aim of this study was to evaluate staff exposure to radon gas in these centers in Tehran in 2015-2016. Materials and Methods: This is a descriptive,  cross-sectional survey. In radiotherapy centers of Tehran, 32 radon gas diffusion chamber detectors were installed for a period of 3 months. After collecting the detectors, radon gas concentrations were calculated. The annual effective dose of personnel was evaluated using staff's working hours per week.   Results: The minimum and maximum concentrations recorded in this study during one year were 22.14 and 398.52 Bq/m3, respectively, with an average of 87.01 ± 80.68 Bq/m3. Also, radiotherapy personnel's annual effective dose was 0.34 ± 0.43 mSv per year with the minimum and maximum amounts of 0.02 and 2.35 mSv per year, respectively. Conclusion: The results indicate that radon level in radiotherapy centers and also that the annual effective dose of personnel in these centers are permissible, and no special action is needed. However, if more attention is paid to certain factors such as air-conditioning, the amount of the gas can even be brought to less than this limit.